EnvironmentalQualityofRSUDinSupportingGreenHospitalInitiatives: A 2025 Case Study - Rudi Ruhdiat (Jurnal Ragam Pengabdian, 2026)
The green hospital concept emphasizes environmentally friendly hospital management that is safe for patients and health workers, and sustainable. Thisstudyaimstoevaluateindoorairquality,particulatematter,noise,and water quality at RSUD Kabupaten Bekasi in 2025, referring to the Ministry ofHealthRegulationNo.2of2023andrelatedqualitystandards.Theresults show that several parameters exceed the quality standards, including CO₂ concentration, PM₂.₅, environmental noise, BOD, COD, DO, mercury, lead, and total detergent. These findings form the basis for technical recommendations to support the transformation towards a green hospital